2020
DOI: 10.3389/fphys.2020.00061
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic agrp and pomc mRNA Responses to Gastrointestinal Fullness and Fasting in Atlantic Salmon (Salmo salar, L.)

Abstract: The orexigenic agouti-related protein (AgRP) and the anorexigenic pro-opiomelanocortin (POMC) are crucial players in the control of feed intake in vertebrates, yet their role in teleosts has not been fully established. Triplicate groups of Atlantic salmon (Salmo salar) post smolts were subjected to (1) fasting for 3 days (fast) and (2) normal feeding (fed), resulting in a significant (p < 0.05) upregulation of hypothalamic agrp1 transcripts levels in the fast group. Moreover, the mRNA abundance of agrp1 was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 44 publications
4
20
1
Order By: Relevance
“…A similar effect was described in common carp (Wan et al, 2012). In contrast, in our recent study, hypothalamic agrp1 was upregulated after 3 days of fasting in Atlantic salmon (Kalananthan et al, 2020). However, in the current study, no differences were observed in the hypothalamus or other regions between the fed and fasted groups for either agrp1 or agrp2.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…A similar effect was described in common carp (Wan et al, 2012). In contrast, in our recent study, hypothalamic agrp1 was upregulated after 3 days of fasting in Atlantic salmon (Kalananthan et al, 2020). However, in the current study, no differences were observed in the hypothalamus or other regions between the fed and fasted groups for either agrp1 or agrp2.…”
Section: Discussionsupporting
confidence: 79%
“…Minimal or no effects of fasting on the mRNA expression of the investigated genes suggest that they play a minor role in the central control of appetite in the short 4 days’ fasting. However, a high individual variability was observed in both fed and fasted experimental groups, which might have led to a possible deviation in the results from our recent study on hypothalamic agrp1 in Atlantic salmon ( Kalananthan et al, 2020 ). Among the factors that contribute to the differences in feed intake, the feeding rate, frequency and time, and social relationships between conspecifics are the result of stimulating competition for a feed resource among individuals ( Attia et al, 2012 ).…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…In our analysis, no correlation was found between stomach content and ghrl mRNA expression levels (stomach is the compartment where ghrl is mostly expressed) but, rather, between mRNA expression in the PSt and inner content in HG. A previous study indicated a correlation between a complete empty stomach with an increase in only one orexigenic factor (i.e., agrp1 mRNA expression levels) in the hypothalamus of 3 days of induced fasting in Atlantic salmon ( Kalananthan et al, 2020b ), supporting the hypothesis that 4 days of fasting are not sufficient to initiate a significant response. Thus, it is still uncertain how the multiple gastric and intestinal signaling factors responds to fasting with different durations.…”
Section: Discussionmentioning
confidence: 73%